English in Finland : a case study of globalization's impact on higher education - Hipke, Sandra (2015)
This paper looks at how the process of globalization, via the Bologna Process has changed higher education in Finland. It examines how legislation was changed, altering the structure of the degree programs, which led to the creation of international degree programs. These programs brought international staff and students to the universities. Many universities have since adopted a language policy to ensure the language rights of all staff and students at the universities.